Evaluasi Usability E-Learning Universitas Qamarul Huda Menggunakan System Usability Scale (SUS) - Valian Yoga Pudya Ardhana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The need for e-learning to support the learning process in higher education is very high, not least at Qamarul Huda University. Qamarul Huda University's e-learning has been running but has not been evaluated and tested for its effectiveness, convenience and usefulness for users, in this case students. In this study, the quality of e-learning that will be measured by users, namely students from the University of Qamarul Huda, is based on measuring the quality of e-learning using the System Usability Scale (SUS). The usability evaluation of e-learning was carried out to collect opinions from different respondents regarding the usefulness of e-learning. In accordance with these problems, it is necessary to evaluate the usability of e-learning at Qamarul Huda University in order to determine the feasibility of the system whether e-learning is easy to use by students, how quickly students can easily understand and use e-learning, whether students still experience many problems or difficulties. in using e-learning. Based on the results of distributing questionnaires or questionnaires to 50 students where different study programs and classes as users of e-learning to get the level of student satisfaction with the e-learning system, it is obtained a score of 71.15 which is in the C grade category falls into the Acceptable range. . With this value, the Qamarul Huda University e-learning system is fairly good and feasible for students to use.